State of the art on animal embryonic chimeras - Razza, Eduardo M.; Emanuelli, Isabele Picada; Barros, Ciro M.; Nogueira, Marcelo Fábio Gouveia [UNESP] (My University, 2013)
Embryonic chimerism is generally used in basic research and in vivo diagnosis of undifferentiated embryonic stem cells (ESC), mostly using mice embryos, although there have been reports in the literature on using rat, rabbit, sheep, chicken, primate, bovine, goat and pig embryos. Several techniques can currently be used to produce chimeric embryos, including microinjection, co-culture with ESC, fusion and aggregation. Although microinjection is the most commonly used method in mice, the mere aggregation of embryos with ESC may result in viable chimeras and be as efficient as microinjection. In mice, this chimerism technique has been shown to have the advantage of aggregating embryos in different stages of development with different ploidy, in addition to using ESC in the tetraploid complementation assay. Compared to other techniques for producing chimeras, the aggregation technique is a cheaper, faster and easier methodology to be performed. Moreover, aggregation can be simplified by chemically removing the zona pellucida with pronase or acidic Tyrode’s solution and be enhanced by using the Well of the Well culture system in combination with adhesion molecules, such as phytohemagglutinin. The most commonly used stages for chimerism by aggregation are those that precede the full compaction of the morula. In these stages, embryos have low-tension adherent junctions at the tangential point between two blastomeres. During the embryonic development of mice, the inner cell mass differentiates into epiblast and hypoblast. These layers will originate the fetal tissues and a portion of the extraembryonic tissues (yolk sac, allantois and amnion), whereas the trophectoderm (TE) gives rise to the chorion. A functional TE is essential for the complex molecular communications that occur between the embryo and the uterus. Embryos produced by somatic cell nuclear transfer, such as commercial cattle clones or endangered species, are subject to large fetal and neonatal losses. Hence embryo complementation with heterologous TE could be of assistance to decrease these losses and might as well assist development of high-value embryos in other approaches.
Keywords: Embryonic chimera; Mammalian embryo; Review